(1241) Economic integration among socialist countries التكامل الاقتصادي بين الدول الاشتراكية - Grote, Gerhard (The Institute Of National Planning., 2018)
Increasing internationalization of the economic life is one of the phenomena of the economic development in the second half of this century, resulting above all from necessities of the scientific-technical revolution and its requirements as to the national economies.